2002
DOI: 10.1023/a:1023285422278
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our infection rate of DJS and urine is 18% which is not very high. Routine DJS cultures are not needed as the same microorganisms grow in urine cultures. No age or sex relation to the infections is found. Antibiotic prophylaxis is effective in preventing clinically ouvert infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
3
10
0
1
Order By: Relevance
“…It remains controversial whether simultaneous DJC cultures are necessary. Some studies have suggested that the results of DJC cultures are consistent with the results of urine culture because bacteria that colonize DJCs can be released into urine; 39 , 40 conversely, some studies have shown that the detection rate was much higher for DJC culture than for bladder urine culture, and the detected pathogens may differ between culture methods. 3 , 41 In this study, patients did not undergo both culture analyses simultaneously; thus, we could not draw a definitive conclusion regarding this point.…”
Section: Discussionmentioning
confidence: 94%
“…It remains controversial whether simultaneous DJC cultures are necessary. Some studies have suggested that the results of DJC cultures are consistent with the results of urine culture because bacteria that colonize DJCs can be released into urine; 39 , 40 conversely, some studies have shown that the detection rate was much higher for DJC culture than for bladder urine culture, and the detected pathogens may differ between culture methods. 3 , 41 In this study, patients did not undergo both culture analyses simultaneously; thus, we could not draw a definitive conclusion regarding this point.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, resistance was significantly higher in patients with a urinary catheter (P = 0.001). A urinary catheter, as well as double ''J'' urinary stents, are responsible for the appearance of NAUTIs [11,12]. The effectiveness of closed urinary drainage systems in preventing UTIs has been established [13].…”
Section: Discussionmentioning
confidence: 99%
“…It concerns both the presence of colonization and the type of pathogen cultured from the Double–J catheters and the urine sample. Available data is controversial, therefore it seems that there is a place for further studies in this field [9, 10]. …”
Section: Introductionmentioning
confidence: 99%